Vitamin D Levels in Epilepsy Patients at the Neurology Polyclinic, Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Sri Handayani; Partan, Radiyati Umi; Zen Hafy; Fitri Octaviana; Citra Ananta Avis; Rini Nindela; Selly Marisdina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: In epilepsy patients, treatment is often lifelong and anti-epileptic drugs (AEDs) can be divided into two general groups, namely drugs that affect cytochrome P-450 (CYP-450) such as carbamazepine, phenytoin, primidone, or valproic acid, and those that affect minimal cytochrome P-450 such as gabapentin, vigabatrin, levetiracetam, oxcarbazepine, or topiramate. AEDs include various drugs that can cause a decrease in vitamin D levels. Therefore, this study was aimed at examining vitamin D levels in epilepsy patients who took AEDs at the neurology polyclinic at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This research is a descriptive study with a cross-sectional design using primary data obtained from the results of patient examinations using laboratory tests and secondary data from medical records. Results: As many as 78% (14 subjects) who received monotherapy had vitamin D levels below normal, and 16 subjects, or 76%, who received polytherapy had vitamin D levels below normal (p = 0.907). A total of 13 (72%) subjects who received phenytoin had vitamin D levels below normal, as well as 5 (63%) subjects who received carbamazepine and 12 (92%) subjects who received other therapies (p = 0.235). A total of 12 (67%) subjects who received therapy for 1-3 years and 18 (86%) subjects who received therapy > 3 years had vitamin D levels below normal (p = 0,406). Conclusion: Vitamin D deficiency is a crucial problem in epilepsy patients receiving AED therapy, where more than 75% of patients have vitamin D deficiency. In this study, vitamin D deficiency did not have a significant relationship with the type of therapy (monotherapy or polytherapy) or the type of drug used. used, duration of therapy, and frequency of sun exposure.